A review of thickness-induced evolutions of microstructure and superconducting performance of REBa2Cu3O7−δ coated conductor - Lin, Jian-Xin; Liu, Xu-Ming; Cui, Chuan-Wei; Bai, Chuan-Yi; Lu, Yu-Ming; Fan, Feng; Guo, Yan-Qun; Liu, Zhi-Yong; Cai, Chuan-Bing (Advances in manufacturing, 2017)
The research and development of high temperature superconducting (HTS) films, especially ReBa 2 Cu 3 O 7 − δ (REBCO or RE123; RE=Y, Gd, or other rare earths) yttrium-based coated conductors, has generated widespread interest for the potential applications of the second generation superconducting films. In view of commercialization, however, the maximum superconducting currents for coated conductors should be increased further. Unfortunately, it has been frequently observed that the average critical current density J c decreases with an increase in film thickness. The thickness effect is still a hurdle for large-scale production, especially in pulsed laser deposition and metal organic deposition processes. An engineering current of more than 1 000 A/cm is desired owing to the high cost of 2G superconducting materials. The present work attempts to review the evolution of various issues subject to the thickness effect, including the microstructure, epitaxial texture, surface roughness, pinning force, oxygen deficiency, residual stress, copper-rich layers, and segregation of elements. Furthermore, recent progress in enhancing the performance of superconductors especially in terms of critical current density is illustrated, such as the use of heavy doping. Further understanding of the thickness effect is extremely important for large-scale commercial development of the second generation high temperature superconductors.